A checklist of the family Pratylenchidae Thorne, 1949 from Iran - Alvani, Somaye; Mahdikhani-Moghadam, Esmat; Rouhani, Hamid; Mohammadi, Abbas (Zootaxa, 2016)
The Family Pratylenchidae comprises nematodes that are capable of penetrating and feeding on internal root tissues. The list of Pratylenchidae species known from Iran is presented. The updated species list provides information on their morphometrics, referring to full or partial descriptions, associated plants, geographical distribution and references. The list includes 37 species belonging to five genera. Two species of Pratylenchus (P. sensillatus and P. wescolagricus) are new records for the Iranian nematofauna. Some information on these two and other known species is also provided.